Influence of sloping tea fields on soil moisture migration. Issue 17 (2018) - Pengfei, Liu; Yongguang, Hu; Feng, Jiang; Sheng, Wang
Abstract: In order to explore the influence of sloping tea fields on soil water migration, this paper studied the characteristics of water transport in soil moisture infiltration and redistribution under different slope gradients (0°, 5° and 15°) and with or without tea plants (Camellia Sinensis L). The results of the experiment showed that in the process of water infiltration, the time required for moisture to infiltrate to the same depth varies with different gradients with or without tea plants. In the absence of tea plants, the time required for water infiltration to the same depth increased first and then decreased with the increase of slope. When tea plants were planted, the time required for water to infiltrate to the same depth increased with increasing slope. In the process of water redistribution, under the same depth of infiltration, the moisture depth of without tea plants increased first with the increase of slope, and then decreased. The moisture depth with tea plants increased with the increase of slope. When the slope was in the range of 0° to 5° and moisture infiltrated to the same depth, the final moisture depth without tea plants was deeper than that with tea plants. When the slope was 5° to 15° and the water infiltrated to the same depth, the final moisture depth without tea plants was shallower than that with tea plants.